Analysis of Genetic Structure of Wild and Cultured Giant Freshwater Prawn (Macrobrachium rosenbergii) Using Newly Developed Microsatellite - Yu, Lingyun; Zhu, Xinping; Liang, Jianhui; Fan, Jiajia; Chen, Chen (Frontiers in Marine Science, 2019)
The giant freshwater prawn (GFP), Macrobrachium rosenbergii, is one of the most critical crustacean species cultured in Southeast Asia. Investigation of the genetic structure of current commercial stocks allows GFP breeding programs to better manage crosses and germplasm banks as well as to promote the rational use of GFP. In the present study, we aimed to characterize and use 17 microsatellite loci, including 12 novel loci derived from GFP transcriptome data, to assess genetic diversity in a wild (Myanmar) and six cultured populations (i.e., four Chinese (Zhejiang, Guangxi, and Guangdong A and B), one Malaysian, and one Thailand’s cultured population). The results showed that the number of alleles per locus ranged from 3 to 18. The mean observed heterozygosity (0.363 ± 0.048) was less than the expected heterozygosity (0.637 ± 0.048). The mean values of polymorphism information content among the seven populations were > 0.5 (ranging from 0.110 to 0.915). These cultured populations exhibited reduced genetic diversity when compared with that of the wild population. Pair-wise genetic differentiation ranged from 0.006 to 0.131 within the seven populations. The dendrogram based on genetic distance showed that six cultured populations were distributed on the same major branch, suggesting that they have a close genetic distance, whereas the wild population was distributed on an independent branch. The results provide a baseline assessment of genetic diversity in some available stocks and lay a foundation for future research efforts toward genetic monitoring and selective breeding.